Financial Literacy in Rich Dad Poor Dad book by Robert Kiyosaki - Sahputra, Juliandi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Rich dad poor dad is one of Robert Kiyosakiâ€™s best seller book that has been translatd in many languages. This study aims to find out the financial literacy in Rich dad Poor dad book. The results of this study found that there are two financial literacy: First one to understand assets vs liabilties an the second one is the poor mindset vs the rich mindset. Â This book is This book does not only give us knowledge about how money works but also open our perpective ho to manage our income as an individual.